2023
DOI: 10.1186/s13014-023-02232-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-classic radiation-induced liver disease after intensity-modulated radiotherapy for Child–Pugh grade B patients with locally advanced hepatocellular carcinoma

Abstract: Background The incidence of classic radiation-induced liver disease (cRILD) has been significantly reduced. However, non-classic radiation-induced liver disease (ncRILD) remains a major concern following radiotherapy in patients with hepatocellular carcinoma (HCC). This study evaluated the incidence of ncRILD following intensity-modulated radiotherapy (IMRT) for Child–Pugh grade B (CP-B) patients with locally advanced HCC and established a nomogram for predicting ncRILD probability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Age, tumor number, and PT were found to be optimal predictors for ncRILD to construct an effective model. Moreover, the tumor number and PT were the most significant factors associated with ncRILD for patients with Child–Pugh grade B with HCC after IMRT [ 34 ]. According to the model, the probability of ncRILD was relatively low for patients with lower scores, which predicts the safety of RT.…”
Section: Discussionmentioning
confidence: 99%
“…Age, tumor number, and PT were found to be optimal predictors for ncRILD to construct an effective model. Moreover, the tumor number and PT were the most significant factors associated with ncRILD for patients with Child–Pugh grade B with HCC after IMRT [ 34 ]. According to the model, the probability of ncRILD was relatively low for patients with lower scores, which predicts the safety of RT.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy has gradually become one of the main treatment methods for unresectable HCC. 71 , 72 However, the efficacy of adjuvant radiotherapy for HCC after curative hepatectomy remains controversial. A randomized trial (n=119) found that adjuvant radiotherapy was technically feasible and relatively safe for centrally located HCCs after narrow-margin hepatectomy but did not improve RFS and OS.…”
Section: Unanswered Questions Of Adjuvant Treatmentmentioning
confidence: 99%